2021
DOI: 10.1038/s41467-021-24621-8
|View full text |Cite
|
Sign up to set email alerts
|

The active sites of Cu–ZnO catalysts for water gas shift and CO hydrogenation reactions

Abstract: Cu–ZnO–Al2O3 catalysts are used as the industrial catalysts for water gas shift (WGS) and CO hydrogenation to methanol reactions. Herein, via a comprehensive experimental and theoretical calculation study of a series of ZnO/Cu nanocrystals inverse catalysts with well-defined Cu structures, we report that the ZnO–Cu catalysts undergo Cu structure-dependent and reaction-sensitive in situ restructuring during WGS and CO hydrogenation reactions under typical reaction conditions, forming the active sites of CuCu(10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 50 publications
5
94
0
Order By: Relevance
“…Various ZnO gas sensors have been researched extensively and the detected gases include CO, NO 2 , NH 3 , H 2 S, ethanol, acetone, formaldehyde and so on [ 68 , 69 ]; according to the characteristics of the used ZnO materials, they can be roughly divided into conventional n-type ZnO nanomaterials, specially doped ZnO nanomaterials and some ZnO complexes. In addition, some studies have shown that suitable irradiation could enhance the performance of ZnO gas sensors.…”
Section: Research Progress Of Zno Nanosensormentioning
confidence: 99%
“…Various ZnO gas sensors have been researched extensively and the detected gases include CO, NO 2 , NH 3 , H 2 S, ethanol, acetone, formaldehyde and so on [ 68 , 69 ]; according to the characteristics of the used ZnO materials, they can be roughly divided into conventional n-type ZnO nanomaterials, specially doped ZnO nanomaterials and some ZnO complexes. In addition, some studies have shown that suitable irradiation could enhance the performance of ZnO gas sensors.…”
Section: Research Progress Of Zno Nanosensormentioning
confidence: 99%
“…In addition, bimetallic Ag-Au based catalysts also present a high catalytic activity for oxidative reactions, such as methanol coupling [25,26] or CO oxidation [27], where the oxygen activation is the key reaction step [28,29]. Moreover, atmospheric contaminants such as CO can be also eliminated through its hydrogenation toward valuable products, such as methane or higher hydrocarbons or alcohols [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The WGSR has received increasing attention in the removal of nocuous CO to obtain pure hydrogen for fuel cells. 3–9 This reaction is a reversible exothermic reaction (CO + H 2 O ↔ CO 2 + H 2 , Δ H = −41.2 kJ mol −1 ), which is thermodynamically favored at low temperature, while faster reaction rates can be achieved at higher temperatures due to kinetic limitations. 10 Even though this reaction is incompatible in dynamics and thermodynamics, the high CO conversion could be obtained by two-stage system in industry.…”
Section: Introductionmentioning
confidence: 99%
“…On account of broad applications and significance of the WGSR, numerous studies have been devoted to develop high-efficiency catalytic systems, in which various oxides or carbides supported the metal phase. 4–6,12 The Au-based and Pt-based catalysts have been investigated in the LT-WGSR by virtue of their excellent reactivities. 11–13 For instance, Flytzani-Stephanopoulos et al substantiated that alumina- or silica-supported Pt-based catalysts with a moderate amount of alkali addition displayed significantly enhanced activity toward LT-WGSR.…”
Section: Introductionmentioning
confidence: 99%